Analisis Kelelahan Kerja dan Stres Psikologis pada Pekerja Pertambangan dengan Roster Kerja Panjang (Journal of Telenursing (JOTING), 2025)
This study analyzes the relationship between work fatigue and psychological stress in mining workers undergoing a long work roster system. This study uses a quantitative method with a descriptive and analytical approach. The results showed that the weakening of work activities was mainly in the mild fatigue category of 79 people (98.8%), while physical weakening and motivational weakening were all in the low fatigue category of 80 people (100%). Meanwhile, in terms of psychological stress, most respondents were in the moderate stress category, such as in the variables of role ambiguity (57.5%), role conflict (65%), quantitative overload (65%), qualitative overload (73.8%), career development (66.3%), and responsibility for others (60%). The results of the Pearson Correlation test showed a correlation coefficient value (r) of 0.510, which indicated a moderate positive relationship between work fatigue and psychological stress. The significance value (p) of 0.000 indicates that the relationship is statistically significant (p